PEMBELAJARAN BAHASA INDONESIA PADA MASA PANDEMI COVID-19 SISWA KELAS X SMA NEGERI 12 SINJAI - Nurfadillah Nurfadillah; Sultan Sultan; Usman Usman (Universitas Negeri Makassar, 2023)
Indonesian Language Learning During the Covid-19 Pandemic in Class X SMA Negeri 12 Sinjai. This study aims to find out how to plan, implement, and evaluate online learning during the Covid-19 period for class X SMA Negeri 12 Sinjai. This research is a qualitative descriptive study. This study's data is divided into three lessons: planning, implementing, and evaluating online learning. The data source used was the Indonesian language teacher at SMA Negeri 12 Sinjai. Data collection is done through interviews and documentation. Data analysis techniques included data reduction, unit arrangement, and categorization. The results of this study produce a description of online learning, specifically in: (1) online learning planning is that the teacher does not prepare new indicators, (2) the implementation of online learning, where the teacher uses a conceptual approachin is the lecture method, and (3) online learning assessment is that the teacher uses the types and forms of online learning assessment.